2020
DOI: 10.1192/j.eurpsy.2020.48
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable source-monitoring impairments in obsessive–compulsive disorder and schizophrenia

Abstract: Background: Based on the observed clinical overlap between obsessive–compulsive disorder (OCD) and schizophrenia (SCZ), both conditions may share, at least in part, common cognitive underpinnings. Among the cognitive deficits that could be involved, it has been hypothesized that patients share a failure in their abilities to monitor their own thoughts (source monitoring), leading to confusion between what they actually did or perceived and what they imagined. Although little is known regarding source-moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…2b). 9,23–66 A detailed description of the exclusion reasons of the 54 excluded studies is available in eTable 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2b). 9,23–66 A detailed description of the exclusion reasons of the 54 excluded studies is available in eTable 4.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, no SM deficits have been reported for conditions where self is preserved, such as major depressive disorder. 34 However, deficits in ISM, but not RM, have been also encountered in patients with obsessive-compulsive disorder, 47 requiring caution in interpreting SM findings as specific for self-disturbances until replicated results from cross-diagnostic studies are available.…”
Section: Source Monitoring and Hallucinationsmentioning
confidence: 99%
“…A study found that both SZ and OCD showed impaired internal source-monitoring abilities, and compared to patients with OCD, patients with SZ had abnormal reality monitoring. These patients all have difficulty tracking their own minds, which causes them to be confused about what they actually did or interpreted and what they envisioned ( 6 ). In conclusion, the results we obtained by NIRS may help us better understand the characteristics of cognitive deficits and insight in SZ and OCD.…”
Section: Discussionmentioning
confidence: 99%
“…SCZ is characterized by consciousness abnormalities including hallucinations, delusions, disorganized speech, decreased motivation, and cognitive deficits (12), while OCD is identified by recurrent intrusive and unwanted thoughts, which result in distress or anxiety and repetitive behaviors (13). The obsessive thoughts in both OCD and delusional ideas in SCZ involved intrusive, unwanted, and foreign thoughts, which indicated the shared failure in monitoring their own thoughts (14). Meta-analysis showed that the total prevalence rate of OCD in SCZ was as high as 12.3% (15).…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of OCD also increases the risk of SCZ (16). Patients with both disorders showed deficient response inhibition (17) and internal source-monitoring deficits (14). As for etiology researches, the common features of the two disorders can be partially explained by shared polygenic risk (8) and shared pathways of glutamate, dopamine, and serotonin (9).…”
Section: Introductionmentioning
confidence: 99%